ORAL AND FOOD HYGIENE HABITS OF SCHOOLCHILDREN IN IASI, ROMANIA - Livia Bobu; Alice Murariu; Edlibi al Hage Walid; Cristina Iordache (Romanian Journal of Oral Rehabilitation, 2018)
The aim of the present study was to assess the oral and food hygiene habits of school children in Iasi in order to establish the necessary preventive measures. Material and methods: The study was cross-sectional and included 533 children aged between 7 and 12 years in Iasi. For the assessment of food hygiene habits, a questionnaire was used to record food consumption over a 4-day period. For oral hygiene assessment, the Silness-Löe bacterial plaque index was used. Results: the highest percentage of the children (43.71%) declared a moderate consumption of carbohydrates. Most of the investigated subjects (61.16%) declared a high frequency of sugar consumption. 45.59% of the children in the study had a less good oral hygiene. Conclusion: The results of the study highlight the need for effective oral health education, addressed not only to children but also to parents and teachers.